STRATEGI HUMAS (PUBLIC RELATIONS) DALAM MENANGANI KOMPLAIN PELANGGAN PADA PELAYANAN PRODUK (Studi Pada Plasa Telkom Malang) - Carmia Diahloka; Akhirul Aminulloh (REFORMASI, 2011)
As the oldest and biggest operator Telkom can not avoid the crisis especially trust crisis to its products and services. The aims of the research is how the Public Relations of Plasa Telkom Malang make strategy to handle complain and what are the resistance factors. This research used descriptive qualitative research method in collecting data by direct observation, documentation and in depth interview with the field informan. To measure the data validity used triangulation technique and data analysis used Miles and Huberman. The research result showed that the strategy used by Public Relations of Plasa Telkom in handling customers complaints are: 1) Quick in response the customers complains, which means not wasting time, 2) Increase the customer service/customer care and security officers services as each functions and responsibilites, 3) Provide Public Relations media such as TV, newspaper, tabloid. The resistance factors of Plasa Telkom Malang Public Relations in handling customer complaints are: 1) The less preparation of Plasa Telkom Malang Public Relations in communications, 2) The less cooperation and approach from the company to the certain media, 3) There is no complete identity from the customers.